Validity and Reliability of the Turkish Version of the Self-Reported Disability Status Scale in Persons with Multiple Sclerosis - Bılek, Furkan; Demir, Caner Feyzi (My University, 2022)
Objective: The aim of this study was designed to investigate the validity, reliability, and cultural adaptation of the Turkish version of the self-reported disability status scale (SRDSS). Materials and Methods: This study was designed as prospective, methodological, and cross-sectional. Turkish translation and cross-cultural adaptation of SRDSS was conducted. SRDSS scores were compared with Expanded Disability Status Scale and Patient Determined Disease Steps to test the concurrent validity. The validity and test-retest reliability of the Turkish SRDSS were investigated in 128 persons with MS. Results: A very strong correlation was found between SRDSS and Expanded Disability Status Scale (r = -0.920, p: 0.000) and Patient Determined Disease Steps (r = 0.857, p = 0.000). The mean of the first test of SRDSS was 1.29 ± 0.59, and the mean of the retest test was 1.30 ± 0.61. A very high correlation was found between test and retest (p < 0.001, r = 0.967). Bland-Altman analysis showed that SRDSS was reproducible with upper and lower limits of agreement of 0.2929 and -0.3089, respectively (bias = -0.008; p = 0.566). Cronbach's alpha coefficient was found to be 0.983 (excellent reliability). For inter-rater agreement, the ICC values in the individual test were 0.967 (954 CI; 0.954–0.977). Conclusion: This study showed that the Turkish version of SDRSS is a valid and reliable measurement tool. In cases where Expanded Disability Status Scale cannot be applied, the Turkish version of SRDSS can be used as an alternative assessment method.
Keywords: Validity; Reliability; Multiple Sclerosis; Self-report; Scale